The legacy of hope summit: a consensus-based initiative and report on eating disorders in the U.S. and recommendations for the path forward - Donald Blackwell (BMC, 2021)
Abstract Background Several unsuccessful attempts have been made to reach a cross-disciplinary consensus on issues fundamental to the field of eating disorders in the United States (U.S.). In January 2020, 25 prominent clinicians, academicians, researchers, persons with lived experience, and thought leaders in the U.S. eating disorders community gathered at the Legacy of Hope Summit to try again. This paper articulates the points on which they reached a consensus. It also: (1) outlines strategies for implementing those recommendations; (2) identifies likely obstacles to their implementation; and (3) charts a course for successfully navigating and overcoming those challenges. Methods Iterative and consensual processes were employed throughout the Summit and the development of this manuscript. Results The conclusion of the Summit culminated in several consensus points, including: (1) Eating disorder outcomes and prevention efforts can be improved by implementing creative health education initiatives that focus on societal perceptions, early detection, and timely, effective intervention; (2) Such initiatives should be geared toward parents/guardians, families, other caretakers, and frontline healthcare providers in order to maximize impact; (3) Those afflicted with eating disorders, their loved ones, and the eating disorders community as a whole would benefit from greater accessibility to affordable, quality care, as well as greater transparency and accountability on the part of in-hospital, residential, and outpatient health care providers with respect to their qualifications, methodologies, and standardized outcomes; (4) Those with lived experience with eating disorders, their loved ones, health care providers, and the eating disorders community as a whole, also would benefit from the establishment and maintenance of treatment program accreditation, professional credentialing, and treatment type and levels of care guidelines; and (5) The establishment and implementation of effective, empirically/evidence-based standards of care requires research across a diverse range of populations, adequate private and government funding, and the free exchange of ideas and information among all who share a commitment to understanding, treating, and, ultimately, markedly diminishing the negative impact of eating disorders. Conclusions Widespread uptake and implementation of these recommendations has the potential to unify and advance the eating disorders field and ultimately improve the lives of those affected. Plain English summary A cross-disciplinary group of eating disorder professionals, thought leaders, and persons with lived experience have come together and reached a consensus on issues that are fundamental to the battle against the life-threatening and life-altering illnesses that are eating spectrum disorders. Those issues include: (1) the need for early detection, intervention, prevention, and evidenced-based standards of care; (2) the critical need to make specialized care more accessible and affordable to all those in need; (3) the importance of developing uniform, evidenced-based standards of care; (4) the need for funding and conducting eating spectrum disorder research; and (5) the indispensability of advocacy, education, and legislation where these illnesses are concerned. During the consensus process, the authors also arrived at strategies for implementing their recommendations, identified likely obstacles to their implementation, and charted a course for successfully navigating and overcoming those challenges. Above all else, the authors demonstrated that consensus in the field of eating spectrum disorders is possible and achievable and, in doing so, lit a torch of hope that is certain to light the path forward for years to come.